Analisis Kelayakan Finansial untuk Peningkatan Kapasitas Produksi UMKM Tahu Kuning - Ana Komari; Lolyka Dewi Indrasari; Venus Khatta Salsabillah (Journal of Research and Technology, 2022)
More than 60 million MSMEs remain actively moving and growing and can even contribute up to 61.07% of the country's economic growth GDP. The potential development of MSMEs needs to be considered again both by the government and the community as a actor in MSMEs in order to develop and grow to compete with other business sectors. In an MSME development plan, it requires capital investment that will be allocated by MSMEs to meet the needs of increasing technology, production and infrastructure facilities. This research was conducted with the aim of conducting financial and non-financial analysis to develop popular yellow tofu MSMEs. This study uses the method of 4 criteria for financial feasibility analysis, namely IRR, NPV, PP, PI and also reviewed technical aspects to determine the feasibility of MSME development. The results of this study show that the plan to increase production capacity in msme yellow tofu is feasible to be implemented with an NPV value of 1,014,825,332>0, an IRR value of 37.1%>5%, a PI value of 10.18>1 and a period of return on investment capital is 2 months 16 days. As well as in terms of technical aspects of the yellow tofu business is worth developing because of the need for equipment, and factory buildings can be fulfilled by using personal costs and realized gradually.